Evaluation of the effects of rehabilitation after surgery using the Ravitch and Nuss methods: a case study - Bal-Bocheńska, Monika Anna; Kądziołka, Wojciech; Rzechonek, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Rehabilitation may be helpful in the prevention of complications associated with the treatment of patients with pectus excavatum who are subjected to surgery using the Ravitch and Nuss methods. This paper presents the case of a patient who underwent successful physical rehabilitation after 8 weeks from the surgery using the combined method. As part of the Nuss procedure, two plates were implanted to form a scaffolding for the patient’s chest, which had previously been corrected with the Ravitch method. The plates were to be removed after 24 months of treatment. After the procedure, in spite of the favorable cosmetic effect of the repair, there was a significant decrease in the spirometric values and physical fitness of the patient. He underwent an individual physiotherapy program, which lasted four weeks. The streamlining of the respiratory system has significantly improved the spirometric values and raised the overall performance of the patient’s organism.